Des éléments d'analyse pour une formation de conseillers d'orientation en intervention interculturelle - Diop, Mamadou (Canadian Journal of Counselling and Psychotherapy, 2007)
Providing an effective multicultural counselling training is becoming an important issue because of increasing cultural diversity among clients. A framework suggested in this article is for analyzing counsellor training for intercultural interventions. The framework consists of the following psychosocial dimensions: (a) issues related to the counsellor, (b) characteristics of a culturally different client, and (c) nature of the intercultural relationship and the sociocultural environment of the relationship.